Lifestyle, Cardiometabolic and Inflammatory markers in Schoolchildren and their Associations with Body Mass Index: Lifestyle, inflammation markers and Children BMI - Ghomari, Lamia; Ghomari-Boukhatem, Hanane; Raiah, Mourad; Boukhari, Youcef; Bouchenak, Malika (Progress in Nutrition, 2022)
Background: Unhealthy lifestyle behaviors are key elements for weight gain, leading to several chronic diseases. The aim of this study was to evaluate lifestyle, cardiometabolic and inflammation markers and their associations with body mass index (BMI) in children.Methods: Schoolchildren (n = 225; G/B = 109/116); aged 7–10 years were recruited. Waist circumference (WC), and BMI were determined. Daily energy intake (DEI), total energy expenditure (TEE), energy balance (EB), physical activity level (PAL), and quality diet using KidMed index were evaluated. Cardiometabolic and inflammatory markers were estimated.Results: Anthropometric classification showed that 62% of children were normal weight (NW), 19% overweight (OW), 9% obese (O), and 10% thin (T). Compared to NW, OW and O presented respectively higher WC (p